Realisasi Kesantunan Berbahasa di Kalangan Santri Pondok Pesantren Yanabiul Qur’an Kecamatan Jombang Kabupaten Jombang - Mochammad Syafiuddin Shobirin; Muhamad Khoirur Roziqin (JoEMS (Journal of Education and Management Studies), 2019)
Islamic boarding schools are one of the non-formal educational institutions that have long term developing Arabic language coaching. Islamic education with diverse communication patterns and prioritizing elements of manners is the main principles of the Yanabiul Qur'an Islamic Boarding School in Jombang District, Jombang Regency. In the Islamic Boarding School, politeness is a cultural phenomenon so that the teachers need to training and educate to their santri in polite language because the teachers have important role when give examples to them, if they don’t habit polite language, so the language can be lost and can be born an arrogant generation, rude generation and drying generation from ethical and religious values. The purpose of this studi is to describe the polite language on santri environment of Yanabiul Qur’an Islamic Boarding School in Jombang District, Jombang. Keywords: Islamic boarding school, politeness language